A framework for automatic intrude object identification in paediatric foreign body aspired radiography images. (2016) - Vasumathy, M.; Thirugnanam, Mythili; Sumathy, S.
At present, radiography plays a significant role in the field of medical image processing. Medical practitioners and radiologists show keen interest in paediatric health informatics especially in foreign body aspiration (FBA). The radiographic techniques such as X-ray, computer topography, magnetic resonance imaging and ultrasound are the commonly used techniques to analyse the interested regions of interest. This paper focuses is in analysing various radiographic techniques used in paediatric FBA with the focus on the significance of radiographic techniques in medical image processing. A framework is proposed to identify and locate the intrude objects in paediatric X-ray images to reduce the misinterpretation in medical diagnosis.